Parametric study to maximize the peak load shifting and thermal comfort in residential buildings located in cold climates. (August 2020) - Luo, Jianing (Tom); Joybari, Mahmood Mastani; Panchabikesan, Karthik; Haghighat, Fariborz; Moreau, Alain; Robichaud, Miguel
Highlights: Conducted a parametric study on an electrically heated floor operated by a self-learning control system. Considered concrete/insulation thickness, floor/air limit temperature, and fan speed as the parameters. Proposed a trade-off Taguchi-ANOVA approach for multi-objectives: peak shifting, thermal comfort and cost saving potential. Among all the factors, insulation thickness was found to have the highest significance. Abstract: In recent years, several peak load-shifting strategies were proposed to bridge the temporal mismatch between energy supply and demand in residential buildings. In cold climate regions (e.g., Quebec), most residential buildings are constructed with wood and are considered light-weight buildings. In such buildings, concrete slabs in the basement have the highest energy storage capacity, and hence, possibilities for peak load shifting (through energy storage) in all the floors of the building are limited. In this regard, a forced ventilation system or heat extraction system (HES) was proposed in the literature to transfer the hot air from the basement to other floors. Though the solution for peak load shifting in the entire house is available, still, the question on optimal conditions to enhance the peak load shifting potential as well as compromises on the thermal comfort and capital cost are left unanswered. Understanding these was the motivation of this study, and subsequently, a parametric study was carried out on the components involved in buried electrically heated floors (BEHFs) integrated with HES. Achieving higher peak shifting while guaranteeing occupants' thermal comfort and lower capital cost were considered as the responses. For the parametric study, five factors namely concrete slab thickness, insulation thickness, fan speed as well as the upper limit for indoor air temperature and floor surface temperature were considered with three levels. The simulation results showed that for most of the cases, insulation thickness had the most significant effect among the factors. The main finding of this research is providing insights on overall optimal conditions for selecting the BEHF and fan parameters to achieve higher peak shifting potential and thermal comfort with a lesser capital cost. Since there are around 1.6 million detached houses in Quebec (with similar building characteristics considered in this study), the obtained optimal conditions can be used as a guideline for both supply and demand sides to achieve higher peak shifting, thermal comfort and heating cost savings.